Natives’ and immigrants’ fertility intentions in Europe: the role of employment - Alderotti, Giammarco (Université de Lille, 2022)
In several European countries, births to immigrant women represent more than 10% of all births [Sobotka 2008]; however, there is evidence showing that in the aftermath of the Great Recession migrants’ fertility might have fallen more pronouncedly among migrants than natives [Sobotka 2017].With this study, we aim to provide further evidence about the employment/fertility link among migrants by focusing on the relationship between employment and fertility intentions - instead of the behaviours. In fact, most research on migrant fertility has focused on childbearing behaviours, disregarding the ideational dimensions represented by attitudes and intentions, which are of primary importance to complete the picture through a better understanding of the normative side of fertility [Milewski and Mussino, 2018]. We do this relying on data from the European Social Survey and focusing on two years, 2004 and 2010, i.e. just before and just after the 2008 financial crisis (the ’Great Recession’). The analysis of developments over this short period allows us to understand the link between fertility intentions and employment in a period characterised by a severe economic crisis. Scrutinising the fertility intentions of migrants with different employment status across Europe, we aim to shed light on dynamics around migrants’ childbearing in the host country.